2018
DOI: 10.4103/jispcd.jispcd_29_18
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of different endodontic sealers against Enterococcus faecalis: An In vitro study

Abstract: ObjectiveThe aim of this in vitro study is to compare the antimicrobial efficacy of four different endodontic sealers against Enterococcus faecalis.Material and Method:Four different endodontic sealers, namely, resin based (AH Plus), zinc oxide-eugenol based (Tubliseal), calcium hydroxide based (Sealapex), and mineral trioxide aggregate (MTA Fillapex) based were tested for their antimicrobial efficacy against E. faecalis using agar diffusion method. Four wells were made by the removal of agar at equidistant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
(25 reference statements)
0
10
0
5
Order By: Relevance
“…28 However, MTA has no obvious antibacterial activity and cannot effectively kill E. faecalis, S. aureus, E. coli or other anaerobic bacteria, and it is difficult to enter the narrow and curved root canal and dentin tubules to remove the bacteria. 29 Pompermayer et al found that MTA was not effective against multispecies microcosm biofilms including E. faecalis, Streptococcus salivarius (S. salivarius), Streptococcus mutans (S. mutans) and so on. 30 In this study, the E. faecalis biofilms treated with MTA was still intact, and the proportion of live bacteria was high, suggesting that MTA had no obvious antibacterial effect on E. faecalis biofilms, which was similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, MTA has no obvious antibacterial activity and cannot effectively kill E. faecalis, S. aureus, E. coli or other anaerobic bacteria, and it is difficult to enter the narrow and curved root canal and dentin tubules to remove the bacteria. 29 Pompermayer et al found that MTA was not effective against multispecies microcosm biofilms including E. faecalis, Streptococcus salivarius (S. salivarius), Streptococcus mutans (S. mutans) and so on. 30 In this study, the E. faecalis biofilms treated with MTA was still intact, and the proportion of live bacteria was high, suggesting that MTA had no obvious antibacterial effect on E. faecalis biofilms, which was similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, data about the antimicrobial efficacy of each group could not be extracted precisely. We contacted the corresponding authors in cases when additional data were required [27,4453], but most of them did not reply after the second email. One author [47] replied and wrote that disclosure of raw data is against their policy.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used antimicrobial test was the agar diffusion test (ADT) [33,34,38,45,48,50,52,53,59–61]. Nine studies used the direct contact test (DCT) [16,36,40,46,50,5658,62], where colony forming units (CFUs) were counted.…”
Section: Resultsmentioning
confidence: 99%
“…Esses materiais possuem diferentes propriedades e composições, como a atividade antimicrobiana observada nos cimentos à base de cimentos de óxido de zinco e eugenol e a base de hidróxido de cálcio, e a adesão, nos cimentos à base de cimentos ionômeros de vidro e resina. No entanto, não existe um único cimento que contemple todas as propriedades desejadas (Dalmia et al, 2018).…”
Section: Introductionunclassified